CGull: A Non-Flapping Seagull-Inspired Composite Morphing Drone - Peter L. Bishay; Moises Brambila; Alex Rini; Peter Niednagel; Jordan Eghdamzamiri; Hariet Yousefi; Joshua Herrera; Eric Bertuch; Caleb Black; Donovan Hanna; Ivan Rodriguez; Youssef Saad; et al. (Proceedings, 2024)
Introduction: Many avian species are well equipped for dynamic flight with flexible morphing wings and tails that optimize aerodynamic performance across various environmental conditions [...]